ANALISIS NILAI-NILAI RELIGIUS DALAM FILM OMAR & HANA - Widya Dewi Arini; Baso Helmi Baharuddin (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2022)
The purpose of this research is to find out and describe the religious values in the film Omar & Hana. This study uses library research methods, with the type of research that is library research. Based on the analysis that has been done, it can beconcluded that the religious values in the film Omar & Hana can be categorized into several values, namely: 1) the value of faith, in the episode "let's give greetings" explains about strengthening friendship; the episode "everything is worship" explains about intending all that is done for Allah swt; the first halal episode explains about viewing a food or beverage halal certificate; the pillars of Islam episode explains that the pillars of Islam are the pillars of religion; our friend's al-Quran episode explains about making the Koran a friend wherever you are. 2) moral values, in the episode "let's give greetings" explains commendable morals in which greetings are exchanged; the episode "everything is worship" explains commendable morals intending all work for Allah swt; Halal episode to explain commendable morals by first viewing the halal logo and certificate for food or beverages; the pillars of Islam episode describes commendable morals in which the pillars of Islam are the pillars of religion; episode al-Quran Kawan Kita explains about commendable morals so that humans make the Koran as a friend throughout their life. 3) The value of Worship in the episode "let's give greetings" explains mahdah worship or actions that are determined by conditions and pillars; the episode "everything is worship" explains mahdah worship intending all work only for Allah swt; the halal ke episode explains about the worship of ghairumahdah, an act that brings goodness and is carried out with sincere intentions because of Allah swt; the episode of the pillars of Islam explains about the worship of mahdah; the pillars of Islam are the pillars of religion; our friend's al-Quran episode explains about mahdah worship making it a human friend at all times